Desempeño laboral de los empleados de la importadora JORUA S.A. Babahoyo. - Alvarado Mejía, Juan Carlos (2019)
The company where the investigation was carried out is the importer Jorua SA, is a commercial company dedicated to the wholesale of pharmaceutical products, has 22 workers legally hired with all the benefits required by the law of the labor and safety code social, the objective of the investigation is to investigate the factors that affect the work performance of the employees of the importer Jorua SA in the city of Babahoyo, several problems were detected based on the investigation, such as the lack of communication between employees and bosses, the demotivation of the staff, lack of a physical environment to consume their food at lunch time, lack of leadership by the immediate boss